Analisis Tata Kelola Teknologi Informasi Untuk Mendefinisikan Arsitektur Informasi Dengan Framework COBIT 4.1 (Studi Kasus Instalasi Rawat Jalan RSUD Prov. NTB): Information Technology Governance Analysis to Define Architecture Information Using the COBIT Framework 4.1 Case studies Instalasi Rawat Jalan RSUD Prov. NTB - Media Isti Azzizah; Nadiyasari Agitha; Ida Bagus Ketut Widiartha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2021)
Treatment for outpatient installations (IRJA) NTB provincial hospitals have used hospital management information systems, but this is still not effective. The information system is not effective because registration centred in the main hall. The centralized registration caused the accumulation of patient queues that occurred in each IRJA polyclinic, and this was due to the absence of an integrated queue number between registrations carried out in the main hall and IRJA polyclinics. Therefore, the governance of information architecture processes needs to be applied to optimize information systems. We use COBIT 4.1 to conduct governance. The aim is to get existing and expected outpatients from Prov. NTB Hospital. So, it can help to manage information architecture to perform quality and competitive outpatient services. The results showed the IT processes selected in PO2 (Determine Information Architecture) and AI4 (Activate and Use). We reach the maturity level of all IT processes at level 3 (the specified process) for conditions as they are and 5 (optimized) for conditions that will occur. The level of maturity can help the NTB Provincial Hospital to improve its services.